Sacroiliac joint morphologic changes from infancy to adulthood - Coudert, Pierre; Dubé-Cyr, Roxanne; Chaumoitre, Kathia; Gille, Olivier; Vital, Jean-Marc; Jouve, Jean-Luc; Arnoux, Pierre-Jean; Panuel, Michel; Evin, Morgane (The spine journal, 2019)
Report of sacroiliac morphology changes during growth is limited in the literature and the interest of such morphology and its consequence for surgery is increasing. Aims of this work are (1) to anatomically define the sacroiliac joint (SIJ), and (2) to assess the influence of growth on the sacroiliac morphology and the pelvic parameters. Forty-nine young subjects from 6 months to 18 years old (y/o) and 20 adults aged from 18 to 50 y/o were selected from our institutional patient database. They underwent a computed tomography (CT) examination on a 128-MDCT (GE Healthcare Optima CT660). Transverse CT image datasets were reconstructed, anonymized, and segmented with ITK-SNAP. Landmarks and surfaces were selected and a SIJ orientation analysis was performed using costumed Python scripts. The subjects were divided into four groups: infants (1.9±1 y/o), children (6.9±1.7 y/o), adolescents (13.7±1.8 y/o), and adults (27.3±5.6 y/o). Differences between SIJ orientation were found significant between young subject groups for synovial sacrum SIJ orientation (p<.001) and iliac total SIJ orientation (p=.036). Both orientations of younger subjects were found significantly different from the adult group (p<.035). SIJ synovial sacrum and iliac total orientations correlated significantly with age (p<.03). All orientations correlated with pelvic incidence (p<.04) except for synovial sacrum SIJ orientation (p=.2). No gender or symmetrical differences were found significant in any group. Morphologic definition of the SIJ confirmed the independency of the gender during growth. Such results will be beneficial for the analysis and management of vertebral pathology.